2017
DOI: 10.2147/ijn.s134526
|View full text |Cite|
|
Sign up to set email alerts
|

Antibacterial properties and toxicity from metallic nanomaterials

Abstract: The era of antibiotic resistance is a cause of increasing concern as bacteria continue to develop adaptive countermeasures against current antibiotics at an alarming rate. In recent years, studies have reported nanoparticles as a promising alternative to antibacterial reagents because of their exhibited antibacterial activity in several biomedical applications, including drug and gene delivery, tissue engineering, and imaging. Moreover, nanomaterial research has led to reports of a possible relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
358
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 530 publications
(374 citation statements)
references
References 141 publications
(147 reference statements)
8
358
1
7
Order By: Relevance
“…6 In recent years, gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs), 7 in particular, have been in the focus of increasing interest due to their simple synthesis and desirable biological activities (ie, antitumor, antibacterial, antiviral and antifungal effects). 8,9 We have reported that the cytotoxic features of AgNPs can be exploited to kill p53 tumor suppressor-deficient 10 as well as multidrug-resistant cancer cells, 11 providing some further details to the mechanism of AgNP-induced antitumor actions. In recent years, several studies have also demonstrated that AgNPs, synthesized either by conventional chemical reduction methods, physical techniques or by different biological entities, exhibit potent inhibitory effects against Gram positive and Gram negative bacterial species and induce cytotoxicity in various pathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In recent years, gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs), 7 in particular, have been in the focus of increasing interest due to their simple synthesis and desirable biological activities (ie, antitumor, antibacterial, antiviral and antifungal effects). 8,9 We have reported that the cytotoxic features of AgNPs can be exploited to kill p53 tumor suppressor-deficient 10 as well as multidrug-resistant cancer cells, 11 providing some further details to the mechanism of AgNP-induced antitumor actions. In recent years, several studies have also demonstrated that AgNPs, synthesized either by conventional chemical reduction methods, physical techniques or by different biological entities, exhibit potent inhibitory effects against Gram positive and Gram negative bacterial species and induce cytotoxicity in various pathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have also demonstrated that AgNPs, synthesized either by conventional chemical reduction methods, physical techniques or by different biological entities, exhibit potent inhibitory effects against Gram positive and Gram negative bacterial species and induce cytotoxicity in various pathogenic fungi. 8,12 Green alternatives to harsh reducing chemicals and environmentally benign capping agents have also been developed to reduce the costs of nanoparticle production and to minimize the generation of hazardous wastes upon the synthetic procedures. 13 In a comprehensive study on AgNPs obtained by chemical reduction using coffee and green tea extracts, we proved the remarkable antimicrobial efficiency of such particles, 14 and we showed evidence that the green material used for AgNP synthesis can largely define the physical, chemical and biological characteristics of the produced nanomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology is gaining much attention in the current century due to its capability to modify properties of metals into their nanoscale (10). Recently, researchers have identified nanotechnology as promising to the antimicrobial agent (11). Antimicrobial mechanisms of nanomaterials include disruption of cell membrane, production of reactive oxygen species, and inhibition of enzyme activity, DNA synthesis, and interruption of energy transduction (12).…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanoparticles (AgNPs) possess particular physicochemical properties that determine their extent of cytotoxicity in biological systems [27]. It is well documented that AgNPs exert an antiproliferative effect on cancer cell lines [19,28].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…There are several nanoscale structures coated with plant extracts and their effect on living systems has been extensively studied [60]. [27]. Moreover, AgNPs were synthesized using Albizia adianthifolia leaf extract; the AgNP analysis determined the presence of saponins and glycosides as stabilizing agents [61].…”
Section: Photosynthesismentioning
confidence: 99%